ETIKA AKADEMIK DAN KUALITAS PENDIDIKAN HUBUNGAN DAN IMPLIKASINYA - Btr, Deswita Lestari; Hilwa, Shafwatul; Janira, Ayla Rizki; Akmal, Zidan Choiril; Nasution, Ataina Zulfa (Journal of Community Devation, 2025)
Academic ethics, which include the principles of honesty, integrity, responsibility, and mutual respect, are seen as an important foundation in creating a conducive learning environment and producing quality graduates. This study will explore how violations of academic ethics, such as plagiarism and cheating, can damage the integrity of the learning process and lower the standard of educational quality. In addition, this study will also analyze the implications of enforcing academic ethics on the development of student character, institutional reputation, and graduates' contributions to society. The results of the analysis indicate that violations of academic ethics, such as plagiarism, cheating on exams, and data fabrication, can significantly damage the quality of education by lowering academic standards, inhibiting the development of critical thinking, and reducing trust in the education system. In contrast, strong enforcement of academic ethics is positively correlated with improved learning quality, the development of responsible student character, and the good reputation of educational institutions. The implications of this study highlight the importance of internalizing academic ethics values ​​through clear institutional policies, effective socialization, and consistent enforcement of sanctions in order to realize optimal educational quality.